Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial (Analisis Perbedaan Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial Ã¢â‚¬ÂProduk Pangan Olahan SaguÃ¢â‚¬Â Kondur Petroleum S.A dalam Membentuk Keputusan Mengol - Pamekar, Galuh Gilang (Jurnal ILMU KOMUNIKASI, 2010)
Abstract : The objective of this research is to analyze the differences on the effectiveness of role playing and role model methods applied in social campaign program. Role playing and role model are the methods in social learning theoryÃ¢â‚¬â€œas a part of persuasion theoriesÃ¢â‚¬â€œwhich implicates to behavior change by affecting with modeling and participate of the target adopters. The social campaign Ã¢â‚¬Å“Produk Pangan Olahan SaguÃ¢â‚¬Â adopts these two methods to persuade target adopters to change their behavior as its campaign goal.